2013
DOI: 10.21236/ada578565
|View full text |Cite
|
Sign up to set email alerts
|

Defining Tailored Training Approaches for Army Institutional Training

Abstract: This report had three purposes. The first purpose was to summarize the research literature and determine the major areas of tailored training research. Those areas were ability grouping, learning in small groups, tutoring, microadaptation, learning styles, and aptitude-treatment interactions (ATI). The second purpose was to determine what types of tailored training were most effective and under what conditions. Of the six areas, only learning styles was deemed ineffective. Each of the remaining areas demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Generally, one would expect these moderating variables to have less of an impact if the relationship between experience and job performance is directly linked than if it's predominately indirect. Schaefer and Dyer (2013) concluded that this research has consistently shown that prior knowledge can frequently better predict performance in a narrow domain, such as typify the technical training found in Army Advanced Individual Training (AIT) programs, than general mental ability and job experience alone. However, these findings provide little practical guidance to Army training developers and instructors on how exactly to identify or develop effective predictive measures that could be efficiently used in actual training settings.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Generally, one would expect these moderating variables to have less of an impact if the relationship between experience and job performance is directly linked than if it's predominately indirect. Schaefer and Dyer (2013) concluded that this research has consistently shown that prior knowledge can frequently better predict performance in a narrow domain, such as typify the technical training found in Army Advanced Individual Training (AIT) programs, than general mental ability and job experience alone. However, these findings provide little practical guidance to Army training developers and instructors on how exactly to identify or develop effective predictive measures that could be efficiently used in actual training settings.…”
Section: Resultsmentioning
confidence: 93%
“…An extensive review of published tailored training research by Schaefer and Dyer (2013) pointed out that Cohen (1994) found group interactions were impacted by both the perceived status of group members and the nature of the task or problem. In essence, the nature of a task or problem places greater or lesser emphasis on the unique skills and experiences of individuals within any group based on their relevance to a specific situation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, academic research on BF has largely focused on cognitive tasks, rather than applied, hands-on tasks typical of Army training settings (see Schaefer & Dyer, 2013). This research, routinely carried out in artificial or laboratory conditions, often increased the complexity of a task (e.g., by adding steps, increasing working memory load on any given step, etc.)…”
Section: Backwards Fading Army Tasks and Army Settingsmentioning
confidence: 99%